DEGREE OF CORRELATION BETWEEN CLINICAL, NEUROLOGICAL, NEUROPHYSIOLOGICAL SYMPTOMS OF HEADACHES IN WOMEN OF KASHKADARYA REGION - Kudratova N.B.; Abdullaeva N.N. (Western European Studies, 2024)
Headache is one of the most common symptoms occurring in various diseases for which one should seek medical attention from a neurologist. Bo is the most common form of pain in the world. According to the Washington State Institute for Health Metrics and Evaluation, there were 1.89 billion cases of tension-type headache worldwide in 2016. According to the International Classification of Headache Revision 3 (ISGB-3, 2018), primary pain, in which no organic cause is identified, and secondary pain are due to organic damage to the central nervous system (CNS) or somatic diseases. Craniocerebral tension (CCN) includes a group of other primary cephalgias associated with migraines, autonomic trigeminal cephalgias, and various conditions
Keywords: central nervous system; migraine; cephalgias